Knowledge of HIV/AIDS and sexual behavior among injection drug users compared to non-injection drug users in rehabilitation centres of Kathmandu. - Dhungel,Saurya (2018)
SUMMARY: HIV/AIDS is one of the national priority programs of the country, and injection drug users are one of the key affected populations, so, it is of utmost necessity to keep track of their knowledge regarding HIV/AIDS and of their sexual behaviour. Having said that, unlike, the established role of unsafe syringe use in HIV transmission among injection drug users, the mechanisms of sexual transmissions of HIV among drug users in general are poorly understood. Moreover, having said that IDUs are one of the KAP for whom interventions must be targeted, there have been studies which showed that HIV prevalence among NIDUs in some areas was as high as that of IDUs. Therefore, the study was designed to compare the sexual behaviour and knowledge regarding HIV/AIDS among injection and non-injection drug users. This cross-sectional comparative study was conducted in drug rehabilitation centres of Kathmandu among injection and non-injection drug users admitted there. The sampling technique used was multistage sampling and 96 injection drug users and 100 non-injection drug users were included in the study. Self-administered questionnaire was used to collect information from the respondents which was adapted from questionnaire used in in Integrated Biological and Behavioral Surveillance survey 2015, among injection drug users in Kathmandu Valley. Approval to conduct the study was taken from Ethical review board of Nepal Health Research Council. The study found that there was a significant association between non-injection drug user and not having comprehensive knowledge regarding HIV/AIDS. The odds of non-injection drug users not having comprehensive knowledge was thrice than injection drug users (OR = 3.34; CI = 1.53 - 7.69). Also, education levels of non-injection drug users and their knowledge regarding HIV/AIDS was found to be significantly different. The odds of a noninjection drug user with primary level education having comprehensive knowledge of HIV/AIDS was 77%, 84% and 83% less than non-injection drug users with secondary, higher secondary and bachelor's or higher-level education respectively (OR = 0.23; 0.16; 0.17). Whereas, education level of injection drug user was not found to be significantly associated with knowledge score. In terms of sexual behaviour, condom use at last sex, having an injecting drug using sexual partner and experience of having sex in exchange of money was found to be significantly different between injection and non-injection drug users. The odds of injection drug users using condom at last sexual intercourse with their non-regular partner was 74% less than non-injection drug users (OR = 0.26; CI = 0.12 - 0.56). Likewise, the odds of injection drug users having an injecting drug using non-regular partner was four times more than noninjection drug users in the study (OR = 4.54; CI = 1.7 - 12.1). Moreover, the odds of injection drug users having sex in exchange of money was five times more than noninjection drug users. (OR = 5.32; CI = 1.12 - 24.3). Non-injection drug users also showcased risky sexual behaviour like having concurrent sexual partners and low practice of using condom with regular partners. 30.8% of the respondents among non - injection drug users reported of having sex with a commercial sexual partner in last year. This kind of sexual behaviour coupled with lesser knowledge about HIV/AIDS means that non-injection drug users can also be quite risky for transmitting HIV/AIDS among non-injecting population. Therefore, intervention programs and surveillance surveys must target both these categories of drug users for assessing their status of HIV/AIDS and its knowledge regarding it.